Analysis of Nuclear Energy for Future Power Plants in Indonesia: An Assessment for Sustainable Energy Development: An Assessment for Sustainable Energy Development - Handrata Roy Josia (The Journal of Indonesia Sustainable Development Planning, 2023)
Indonesia has been investing in expanding its power generation capacity to meet increasing needs. There is an ongoing demand for a new source of energy that is reliable, affordable, safe, and clean. This research has assessed the feasibility on implementing nuclear power plants in Indonesia using systematic literature review based on a comprehensive SWOT analysis, IFE/EFE matrix analysis, and TOWS analysis. The obtained result is that the impacts of internal and external factors are assessed as moderate-positive and positive, respectively. The research implies that strategies regarding investments, benefits, waste management, and collaborations with other alternative energy sources can significantly maximize the benefits and overcome challenges. This study contributes to the understanding of nuclear energy implementation in Indonesia and provides insights for policymakers, stakeholders, and researchers seeking to explore and promote sustainable energy solutions in an urgent need regarding increasing energy demand.